Intranasal Drops Of Ketamine versus Midazolam for Preoperative Pediatric Sedation In General Surgical Procedures (Sirte Journal of Medical Sciences, 2022)
Premedication in the pediatric age group presents a challenging situation. The young children are not fully able to understand the necessity for their surgery. Fear of operating theater, injections and separation from parents prior to anesthesia produce traumatic experiences in tend mind of young children. In the past, psychological preparation was only used before surgery. Later on, many drugs like morphine, paraldehyde, meperedine, diazepam and barbiturates have been used.The aim of this study is to compare the effects and the side effects of intranasal ketamine versus midazolam administrated for pediatric premedication.In this study we evaluate and compare intranasal ketamine versus midazolam as premedication in pediatric anesthesia according to  the onset of sedation, degree of sedation , easy cannulation, acceptance of mask before intubation, hemodynamic changes regarding heart rate, mean blood pressure, respiratory rate and intraoperative oral secretion grading.This study was a double blinded randomized controlled study which was carried out at ibn sina Hospitals from February 2018 to January 2020. This study included 54 Child aged from 5 to 8 years admitted to the ibn sina Hospitals for general surgical procedures e.g herniotomy, tonsillectomy and hypospadias etc. All the patients completed the study. Regarding the onset of sedation: the result of this study found that onset of sedation was earlier in the intranasal midazolam as The  onset of sedation for ketamine group and midazolam group was respectively 14.96 ± 3.1 and 8.16 ±2.1. Most patients became sedated 6-10 minutes when compared to intranasal ketamine as most patients sedated after 16-20 minutes. We recommend the use of intranasal ketamine and midazolam as preoperative pediatric sedatives to decrease anxiety of children before start of general anesthesia to overcome drawbacks of pediatric anxiety and fear postoperatively and Intranasal midazolam was better than ketamine according to onset of sedation which started earlier and intraoperative secretions were scanty with midazolam in comparison with ketamine.
Keywords: intranasal ketamine; midazolam; pediatric sedatives